Peran Video Editor dalam Pembuatan Konten TikTok @bogornative pada Media Wiskul Bogor - Asri Yuningsih; Suparman Suparman (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The development of information and communication technology in today’s digital era has had a significant impact on various aspects of life, including the role of video editors. This paper aims to describe the role of video editors in creating TikTok content for @bogornative on Media Wiskul Bogor. The study uses a qualitative approach with an analytical method based on the Multimedia Development Life Cycle (MDLC) theory by Luther-Sutopo (2003), which consists of six main stages: Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The findings show that video editors play an important role in the digital creative industry. Their responsibilities are not only related to the technical aspects of editing but also include the ability to build visual narratives, create engaging story flow, and ensure harmony between visuals, audio, and the designed concept. In addition, video editors are required to understand social media trends to keep the content relevant. Throughout the process, editors often face various challenges such as limited device capacity, large file sizes, miscommunication within the team, and tight deadlines that demand high efficiency and creativity